The spatial aspects of development in south-eastern Europe - George Petrakos; Dimitri Economou (European Regional Science Association (ERSA), 2002)
This paper analyses for the first time the spatial structure of south-eastern Europe in an effort to assess regional imbalances, border conditions, urban hierarchies and detect the adjustments of the region to the forces of integration and transition. The analysis is based on a unique data base compiled from national sources and is carried on with the use of statistical, diagrammatic and cartographic methods. The analysis shows that south-eastern Europe is characterized by increasing regional disparities, an increasingly superior performance of the metropolitan regions, serious discontinuities at the borders which have, in most cases, generated over-time border regions with below average performance and finally an urban system with serious deficiencies in medium sized cities. These findings suggest that regional policy should become a permanent ingredient of indigenous and international development initiatives, which need to pay a greater attention to the needs of border regions, encouraging and promoting programs and policies of cross-border cooperation.
Keywords: 330